Zeely - Hamilton, Virginia 1936-2002.; Shimin, Symeon 1902- (New York Aladdin Books New York Macmillan Publishing, 1987)
Geeder's summer at her uncle's farm is made special because of her friendship with a very tall, composed woman who raises hogs and who closely resembles the magazine photograph of a Watutsi queen.
Keywords: African Americans -- Fiction